2018
DOI: 10.1002/em.22265
|View full text |Cite
|
Sign up to set email alerts
|

Geraniin Differentially Modulates Chromosome Stability of Colon Cancer and Noncancerous Cells by Oppositely Regulating their Spindle Assembly Checkpoint

Abstract: Geraniin has been reported to specifically induce apoptosis in multiple human cancers, but the underlying mechanism is poorly defined. The spindle assembly checkpoint (SAC) is a surveillance system to ensure high‐fidelity chromosome segregation during mitosis. Weakening of SAC to enhance chromosome instability (CIN) can be therapeutic because very high levels of CIN are lethal. In this study, we have investigated the effects of geraniin on the SAC of colorectal cancer HCT116 cells and noncancerous colon epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…38 Like many other DNA-damaging agents, cisplatin not only kills cancer cells but also induces massive damage to normal cells. As strategies to treat cancer have focused primarily on the killing of cancer cells, we have previously found that several phytochemicals such as geraniin and the geraniin-containing herbal drug-Phyllanthus emblica-are able to protect normal but not cancer cells against spontaneous and chemotherapyinduced GIN, [50][51][52][53][54] suggesting a possibility that changes in diet could improve a chemotherapy drug's side effects on normal cells. Indeed, short term starvation has potential to protect normal cells against the cytotoxicity of high-dose chemotherapy 55,56 and multiple cycles of fasting augment the anticancer efficacy of certain chemotherapy drugs via synergistically promoting DNA breaks in cancer cells.…”
Section: Food and Function Papermentioning
confidence: 99%
“…38 Like many other DNA-damaging agents, cisplatin not only kills cancer cells but also induces massive damage to normal cells. As strategies to treat cancer have focused primarily on the killing of cancer cells, we have previously found that several phytochemicals such as geraniin and the geraniin-containing herbal drug-Phyllanthus emblica-are able to protect normal but not cancer cells against spontaneous and chemotherapyinduced GIN, [50][51][52][53][54] suggesting a possibility that changes in diet could improve a chemotherapy drug's side effects on normal cells. Indeed, short term starvation has potential to protect normal cells against the cytotoxicity of high-dose chemotherapy 55,56 and multiple cycles of fasting augment the anticancer efficacy of certain chemotherapy drugs via synergistically promoting DNA breaks in cancer cells.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The SAC (spindle assembly checkpoint) makes sure chromosomes segregate correctly to avoid MC, and the DNA structure checkpoint prevents DNA damage. There are drugs aiming at the SAC or DNA structure checkpoint to induce MC in colon cancer cells, including geraniin [ 30 ], docetaxel, and vincristine, which have a synergistic effect with Aurora inhibitor SNS-314 [ 31 ], a rimonabant that suppresses the progression of colon cancer [ 32 ] and low doses (~0.5 μM) of reversine [ 33 ].…”
Section: Mitotic Catastrophe and Colon Cancermentioning
confidence: 99%